Tocqueville between two worlds : the making of a political and theoretical life - Wolin, Sheldon S. (Princeton University Press, 2003)
"Alexis de Tocqueville may be the most influential political thinker in American history. He also led an unusually active and ambitious career in French politics. In this book, one of America's most important contemporary theorists draws on decades of research and thought to present the first work that fully connects Tocqueville's political and theoretical lives. In doing so, Sheldon Wolin presents sweeping new interpretations of Tocqueville's major works and of his place in intellectual history. As he traces the origins and impact of Tocqueville's ideas, Wolin also offers a profound commentary on the general trajectory of Western political life over the past two hundred years."--Jacket